2021
DOI: 10.3390/medicina57090988
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Perinatal Hypoxia and Asphyxia at an Early School Age

Abstract: Background and Objectives: Late long-term outcomes of perinatal asphyxia (PA) in school-age are often unclear. To assess long-term outcomes at an early school age in children who had experienced perinatal hypoxia or asphyxia, where therapeutic hypothermia was not applied. Materials and Methods: The case group children were 8–9-year-old children (n = 32) who were born at full term and experienced hypoxia or asphyxia at birth, where therapeutic hypothermia (TH) was not applied. The control group consisted of 8–9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Moreover, at 18-22 months of age, epilepsy, blindness, severe hearing impairment, and disabling cerebral palsy were found in 16%, 14%, 6%, and 30% of asphyxiated neonates, respectively (22)(23)(24). Furthermore, these neonates were found to have lower academic performance at 8-9 years of age (25).…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, at 18-22 months of age, epilepsy, blindness, severe hearing impairment, and disabling cerebral palsy were found in 16%, 14%, 6%, and 30% of asphyxiated neonates, respectively (22)(23)(24). Furthermore, these neonates were found to have lower academic performance at 8-9 years of age (25).…”
Section: Introductionmentioning
confidence: 92%
“…Si bien la HT reduce el riesgo de muerte, las secuelas del neuro desarrollo en infantes sobrevivientes con esta condición son diversas, se han reportado alteraciones motoras, cognitivas, neuropsicológicas, conductuales o del lenguaje (Chalak et al, 2021;Dzikienė et al, 2021;Estiphan et al, 2023;Groenendaal et al, 2013;Hortigüela et al, 2024;Martínez-Biarge et al, 2012;Pappas et al, 2015;Pinto et al, 2023;Simbruner et al, 2010;Sutin et al, 2023;Sweetman et al, 2022). Además, de los trastornos en la alimentación derivados de las alteraciones en la succión-deglución, reflujo gastroesofágico, disminución en la motilidad intestinal, hipertono o distonía que afectan la musculatura oro-facial, así como eventos recurrentes de atragantamiento, los cuales determinan cuadros de desnutrición, existe amplia evidencia que la desnutrición en esta etapa temprana de la vida tiene un impacto negativo en el crecimiento físico, considerado indicador relevante de mayor riesgo de alteración en el desarrollo neurológico (Alzamora et al, 2010;Fontaine et al, 2023;Georgieff et al, 2018;Jayakumar et al, 2024;Jensen et al, 2017;Martínez-Biarge et al, 2012Matonti et al, 2020;Park et al, 2023;Prado & Dewey, 2014).…”
Section: Introductionunclassified
“…According to existing data, 20 out of 1000 live births require resuscitation, resulting in clinical and biochemical symptoms of perinatal asphyxia [ 1 , 2 ]. Currently, perinatal asphyxia affects approximately 4 million newborns annually worldwide [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…About 15–25% of these newborns die in the neonatal period, up to 25% of survivors develop neurological deficits, and 10–30% have retarded psychomotor development [ 4 , 5 ]. Studies analyzing the long-term consequences in preschool children after perinatal asphyxia have shown that cerebral palsy develops in 5.5–52% [ 6 , 7 , 8 , 9 ], severe disability in 11–19% [ 6 ], various motor impairments in 1.3–40% [ 2 , 8 , 9 , 10 ], hearing loss in 2–20% [ 6 , 9 , 10 ], vision defects in 1.8–40% [ 6 , 9 , 11 ], speech disorders in 4.2–21% [ 6 , 7 , 8 ], epilepsy in 13%, and cognitive impairment in 31% [ 1 , 2 , 12 ].…”
Section: Introductionmentioning
confidence: 99%